Effects of lysine/ideal protein level on performance, carcass characteristics, digestibility and blood parameters of Duroc barrows from 30 to 50kg - Palhares, L. O.; Dutra Junior, W. M.; Lourenco-Silva, M. [UNESP]; Carmo, M. R.; Serafim, J. E.; Gasparini, S. P.; Lima, T. S.; Holanda, M. C. R. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The objective of this study was to evaluate digestible lysine levels, keeping the relation among amino acids for Duroc barrows from 30 to 50kg. Fifty Duroc barrows (30.35 +/- 1.96kg live weight) were allotted in a completely randomized experimental design, divided in five treatments with five replicates and two animals in each experimental unit. The treatments consisted of digestible lysine levels (0.73%; 0.83%; 0.93%; 1.03% and 1.13%), keeping the relation with other essential amino acids. Performance, carcass characteristics, blood parameters and digestibility of the diets were evaluated. There was a quadratic response on weight gain, feed conversion and creatinine serum concentration as a function of the digestible lysine levels, with the greater levels obtained at 0.92%, 0.93% and 0.93%, respectively. The carcass characteristics were not influenced by the treatments. There was a linear increase of apparent digestibility of crude protein, total serum protein and urea. Results suggest that the requirement of protein and digestible lysine was 16.70% and 0.93%, respectively, providing improvements on weight gain, feed conversion and creatinine serum concentration of Duroc barrows in the growth phase.
Keywords: amino acid; ideal protein; growth phase; nutritional requirements